1980
DOI: 10.1111/j.1471-4159.1980.tb11255.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the First Step of the Initiation of Brain Protein Synthesis by Guanosine Diphosphate

Abstract: Initiation factor elF-2-like activity has been measured in the 0.5 M-KCI wash of rat brain microsomes. Ternary complex formation (eIF-2 . GTP . Met-tRNA,), one of the early steps in protein synthesis initiation, is optimal in a high-[K+], low-"a+] environment. Mgz+, Ca2+, Li+, spermine, and spermidine reduce, and the antibiotic aurin tricarboxylic acid can effectively eliminate ternary complex formation. The formation of ternary complex requires GTP or its nonhydrolyzable analog, GMP-P(NH)P. Ternary complex fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
17
0

Year Published

1981
1981
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 78 publications
0
17
0
Order By: Relevance
“…Compared with levels in adults, the levels of UTP and CTP in neonatal rat brain are significantly higher, which may be related to a high level of synthesis of sugars and lipids (Mandel and Edel-Harth, 1966). Previous reports have shown that a change in the ratio of GTP to GDP affects protein synthesis (Walton and Gill, 1975;Dwyer and Wasterlain, 1980). The ratio of GTP to GDP is also high in neonatal rat brain.…”
mentioning
confidence: 96%
“…Compared with levels in adults, the levels of UTP and CTP in neonatal rat brain are significantly higher, which may be related to a high level of synthesis of sugars and lipids (Mandel and Edel-Harth, 1966). Previous reports have shown that a change in the ratio of GTP to GDP affects protein synthesis (Walton and Gill, 1975;Dwyer and Wasterlain, 1980). The ratio of GTP to GDP is also high in neonatal rat brain.…”
mentioning
confidence: 96%
“…16 Another change could be a slight shift in the activity of polypeptide chain initiation factor eIF2, which participates in the initiation of protein synthesis. The activity of this factor is influenced by the intracellular guanosine triphosphate:guanosine diphosphate ratio, 17 which could be reduced by ischemia. Another possibility is ribosomal damage.…”
mentioning
confidence: 99%
“…Status epilepticus is immature marmosets depletes energy reserves even when seizures do not produce hypoxemia or hypotension [15], but flurothyl status epilepticus in newborn dogs does not [56]. The fall in ATP probably accounts are least in part for the inhibition of protein synthesis observed during seizures in those neonates [48] through a GDP cascade effect mediated by the enzyme nucleotide kinase [12]. …”
Section: Discussionmentioning
confidence: 99%